2019
DOI: 10.3847/1538-4357/ab0177
|View full text |Cite
|
Sign up to set email alerts
|

EBIT Observation of Ar Dielectronic Recombination Lines near the Unknown Faint X-Ray Feature Found in the Stacked Spectrum of Galaxy Clusters

Abstract: Motivated by possible atomic origins of the unidentified emission line detected at 3.55 keV to 3.57 keV in a stacked spectrum of galaxy clusters (Bulbul et al. 2014), an electron beam ion trap (EBIT) was used to investigate the resonant dielectronic recombination (DR) process in highly-charged argon ions as a possible contributor to the emission feature. The He-like Ar DR-induced transition 1s 2 2l -1s2l 3l was suggested to produce a 3.62 keV photon (Bulbul et al. 2014) near the unidentified line at 3.57 keV a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…This claim triggered multiple follow-up papers, intense debates, reinvestigating the excess at the 3.5 keV, or also trying to explain it with different phenomena (e.g., [10][11][12][13][14][15][16][17][18][19]). A recent study [20] found some missing features in the originally used database near the unidentified line. The inclusion of these features raises the total flux value in the region around 3.5 keV but is still not enough to explain the line found in the stacked galaxy cluster spectra.…”
Section: A Sterile Neutrino Dark Mattermentioning
confidence: 98%
“…This claim triggered multiple follow-up papers, intense debates, reinvestigating the excess at the 3.5 keV, or also trying to explain it with different phenomena (e.g., [10][11][12][13][14][15][16][17][18][19]). A recent study [20] found some missing features in the originally used database near the unidentified line. The inclusion of these features raises the total flux value in the region around 3.5 keV but is still not enough to explain the line found in the stacked galaxy cluster spectra.…”
Section: A Sterile Neutrino Dark Mattermentioning
confidence: 98%
“…When reading the literature on the core-excited levels of Li-like ions, one faces a difficulty with heterogeneous spectroscopic notation. In the early papers [7,8] dealing with moderately charged ions, a peculiar kind of LS -coupling scheme was used to designate the 1s2s 2 , 1s2p 2 , and 1s2s2p energy levels, which we will call Gabriel's scheme. For the 1s2p 2 configuration having two equivalent p-electrons it is impossible to distinguish between them, so the two p-electrons are combined first to produce an intermediate singlet ( 1 S or 1 D) or triplet ( 3 P) term, which is then combined with the 2 S term of the 1s shell to produce the final LS term.…”
Section: Coupling Schemesmentioning
confidence: 99%
“…Dielectronic satellite spectra of highly charged ions are an important source of spectroscopic data widely used for analyzing astrophysical plasmas as well as spectra from electron beam ion traps, tokamaks and laserproduced plasmas (see, e.g., [1][2][3][4]). Such spectra provide crucial information on the electron temperature and density, the ionization state distribution, and other characteristics of hot plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…Various non-dark matter, astrophysical explanations for the line have been discussed. Among these interpretations is contamination due to nearby K and Ar dielectric emission, both of which have been evaluated and subsequently ruled out using electron beam ion trap (EBIT) experiments (Bulbul et al 2019;Gall et al 2019;Weller et al 2019). A current leading interpretation is charge exchange (CX) between bare Sulfur ions and neutral Hydrogen, described by Bulbul et al (2014a), Gu et al (2015), Shah et al (2016), and others referenced therein.…”
Section: Dsicilian@umiamiedumentioning
confidence: 99%